Loss of Regulator of G-Protein Signaling 5 Leads to Neurovascular Protection in Stroke. Issue 9 (September 2018) - Özen, Ilknur; Roth, Michaela; Barbariga, Marco; Gaceb, Abderahim; Deierborg, Tomas; Genové, Guillem; Paul, Gesine
Abstract : Background and Purpose—: In ischemic stroke, breakdown of the blood-brain barrier (BBB) aggravates brain damage. Pericyte detachment contributes to BBB disruption and neurovascular dysfunction, but little is known about its regulation in stroke. Here, we investigated how loss of RGS5 (regulator of G protein signaling 5) in pericytes affects BBB breakdown in stroke and its consequences. Method—: We used RGS5 knockout and control mice and applied a permanent middle cerebral occlusion model. We analyzed pericyte numbers, phenotype, and vessel morphology using immunohistochemistry and confocal microscopy. We investigated BBB breakdown by measuring endothelial coverage, tight junctions, and AQP4 (aquaporin 4) in addition to BBB permeability (fluorescent-conjugated dextran extravasation). Tissue hypoxia was assessed with pimonidazole hydrochloride and neuronal death quantified with the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Results—: We demonstrate that loss of RGS5 increases pericyte numbers and their endothelial coverage, which is associated with higher capillary density and length, and significantly less BBB damage after stroke. Loss of RGS5 in pericytes results in reduced vascular leakage and preserved tight junctions and AQP4, decreased cerebral hypoxia, and partial neuronal protection in the infarct area. Conclusions—: Our findings show that loss of RGS5 affects pericyte-related BBB preservation in stroke and identifies RGS5 as an important target for neurovascular protection. Abstract : Supplemental Digital Content is available in the text.